Monetary and banking implications of the shari‘ah emphasis on existence of capital at the outset of joint ventures - Sadique, Muhammad Abdurrahman (2012)
This study attempts to verify the shari‘ah position on existence of capital in the context of joint ventures financed by Islamic banks, based on their current practice. The position of Islamic schools of law on the issue is ascertained from their major sources, and the implications of the shari‘ah requirement examined; the current practice of Islamic banks and the contemporary shari’ah approachs to the issue are scrutinised; the change in the nature and identity of money is analysed to determine whether it is significant in this regard.